Pseudocitrobacter cyperus, a novel bacterial species recovered from Cyperus alternifolius in Egypt - Samira M. Hamed; Mai A. Amer (BMC Microbiology)
Abstract Background Strain Cyp38ST was isolated as an endophyte from the plant Cyperus alternifolius, collected along the banks of the River Nile in 2019. Preliminary analysis tentatively identified Cyp38ST as belonging to the genus Pseudocitrobacter. Methods The preliminary identification of Cyp38ST was performed using the VITEK®2 identification system, MALDI-TOF-MS, and 16S rRNA gene sequencing. To confirm its taxonomic classification, the draft genome of Cyp38ST was generated using DNBseq, and the genome-based taxonomic evaluation was conducted by calculating the overall genome-relatedness indices (OGRIs) such as Average Nucleotide Identity (ANI), digital DNA-DNA hybridization (dDDH), and the tetra-nucleotide signatures (Tetra). Additionally, the biochemical features, antimicrobial susceptibility profiles, and fatty acid methyl ester content of Cyp38ST were characterized. Results VITEK®2 misidentified Cyp38ST as Citrobacter werkmanii, MALDI-TOF-MS identified it as Pseudocitrobacter faecalis. While the 16S rRNA gene showed more than 99.0% similarity to other Pseudocitrobacter species, the calculated OGRIs were lower than the thresholds recommended for species assignment to all currently known Pseudocitrobacter species. Furthermore, the phylogenomic analysis revealed that Cyp38ST forms a distinct species cluster within the genus Pseudocitrobacter. Cyp38ST was predicted as a potential human pathogen and carried a unique ß-lactamase-coding gene. Conclusion Here we present Cyp38ST (= CCASU-2024-73T) as the type strain of a novel species within the genus Pseudocitrobacter to which we propose the name Pseudocitrobacter cyperus sp. nov. We provide a full description of the novel species and present its genome sequence and annotation. The discovery of this novel species highlights the potential of endophytic bacteria associated with unique plant hosts to harbor previously uncharacterized microbial diversity.